Silencing of miR-150-5p Ameliorates Diabetic Nephropathy by Targeting SIRT1/p53/AMPK Pathway - Dong, Wenmin; Zhang, Huiqian; Zhao, Cheng; Luo, Yun; Chen, Ying (Frontiers in Physiology, 2021)
Diabetic nephropathy (DN) is a common complication of diabetes and an important cause of end-stage renal disease. Increasing evidence suggests that miRNAs regulate the development of DN. In a preliminary study, high levels of miR-150-5p were detected in the serum and urine of patients with DN. Consequently, we investigated the effect and mechanism of action of miR-150-5p in DN in vitro and in vivo. Our results showed that inhibition of miR-150-5p reversed high glucose-induced podocyte injury and Streptozocin (STZ)-induced diabetic nephropathy in mice. Further analysis revealed that miR-150-5p targeted the 3’ UTR of sirtuin 1 (SIRT1) consequently decreasing SIRT1 levels in podocytes. Importantly, we found that the silencing of miR-150-5p promoted the interaction between SIRT1 and p53, causing the suppression of p53 acetylation in podocytes and kidney tissue. This resulted in the stimulation of AMPK-dependent autophagy. In conclusion, our study demonstrated that the silencing of miR-150-5p played a reno-protective role in DN mice through targeting SIRT1.